2013
DOI: 10.1016/j.yexcr.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Toward single cell traction microscopy within 3D collagen matrices

Abstract: Mechanical interaction between the cell and its extracellular matrix (ECM) regulates cellular behaviors, including proliferation, differentiation, adhesion, and migration. Cells require the three dimensional (3D) architectural support of the ECM to perform physiologically realistic functions. However, current understanding of cell-ECM and cell-cell mechanical interactions is largely derived from 2D cell traction force microscopy, in which cells are cultured on a flat substrate. 3D cell traction microscopy is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 132 publications
(166 reference statements)
0
83
0
1
Order By: Relevance
“…and coworkers (24). We first measure collagen matrix deformation using a 3D particle tracking microscopy (37,38). Breast cancer cells are embedded within a collagen matrix covalently bonded to fluorescent marker beads (Fig.…”
Section: Measuring Cell Force By Tracking Matrix Deformation and Applmentioning
confidence: 99%
“…and coworkers (24). We first measure collagen matrix deformation using a 3D particle tracking microscopy (37,38). Breast cancer cells are embedded within a collagen matrix covalently bonded to fluorescent marker beads (Fig.…”
Section: Measuring Cell Force By Tracking Matrix Deformation and Applmentioning
confidence: 99%
“…In this work, the bead concentration resulted in a mean particle spacing of approximately 12.5 µm. By comparison, recent work in TFM makes use of mean particle spacings in the range of 1.5 µm to 25 µm, though high sampling frequency methods tend to keep within the 1.5 -3 µm regime [25].…”
Section: Sample Preparation For Effective Cross-correlation-based Dismentioning
confidence: 99%
“…One area of interest is that of collective cellular behavior, where 2D TFM studies have revealed several collective cellular behaviors including wave patterns in cell migration fronts [18], spacefilling behaviors [19], tendencies to minimize intercellular shear stresses [20], and jamming transitions [5,21]. Recent work has led to the development of TFM in 3D cell culture, with confocal microscopy taking the lead as the modality of choice to enable imaging of 3D samples and deformations [15,17,[22][23][24][25][26]. It remains an open area of research how the collective cell behaviors observed in 2D settings will translate within 3D environments.…”
Section: Introductionmentioning
confidence: 99%
“…This is a direct consequence of the scalingκ ∼ ϕ ∝ (a/ l 0 ) 2 , which remains invariant to changes in fibril thickness for a given total protein concentration. The structure of collagen networks, including fibril thickness, mesh size, homogeneity, and presumably connectivity, depends in detail on concentration and polymerization conditions in nontrivial ways [37,38]. However, under the basic assumptions mentioned above,κ remains a constant.…”
Section: Relationship Between Model and Experimental Parametersmentioning
confidence: 99%